Differentially Deregulated MicroRNAs as Novel Biomarkers for Neoplastic Progression in Ulcerative Colitis. Issue 7 (8th July 2022) - Quintanilla, Isabel; Jung, Gerhard; Jimeno, Mireya; Lozano, Juan José; Sidorova, Julia; Camps, Jordi; Carballal, Sabela; Bujanda, Luis; Vera, Maria Isabel; Quintero, Enrique; Carrillo-Palau, Marta; Cuatrecasas, Miriam; et al.
Abstract : INTRODUCTION: Colorectal cancer (CRC) is a potentially life-threatening complication of long-standing ulcerative colitis (UC). MicroRNAs (miRNA) are epigenetic regulators that have been involved in the development of UC-associated CRC. However, their role as potential mucosal biomarkers of neoplastic progression has not been adequately studied. METHODS: In this study, we analyzed the expression of 96 preselected miRNAs in human formalin-fixed and paraffin-embedded tissue of 52 case biopsies (20 normal mucosa, 20 dysplasia, and 12 UC-associated CRCs) and 50 control biopsies (10 normal mucosa, 21 sporadic adenomas, and 19 sporadic CRCs) by using Custom TaqMan Array Cards. For validation of deregulated miRNAs, we performed individual quantitative real-time polymerase chain reaction in an independent cohort of 50 cases (13 normal mucosa, 25 dysplasia, and 12 UC-associated CRCs) and 46 controls (7 normal mucosa, 19 sporadic adenomas, and 20 sporadic CRCs). RESULTS: Sixty-four miRNAs were found to be differentially deregulated in the UC-associated CRC sequence. Eight of these miRNAs were chosen for further validation. We confirmed miR-31, -106a, and -135b to be significantly deregulated between normal mucosa and dysplasia, as well as across the UC-associated CRC sequence (all P < 0.01). Notably, these miRNAs also confirmed to have a significant differential expression compared with sporadic CRC (all P < 0.05). DISCUSSION: UC-associated and sporadic CRCs have distinct miRNA expression patterns, and some miRNAs indicate early neoplastic progression. Abstract :